2019
DOI: 10.1130/b35355.1
|View full text |Cite
|
Sign up to set email alerts
|

Refined Permian–Triassic floristic timeline reveals early collapse and delayed recovery of south polar terrestrial ecosystems

Abstract: The collapse of late Permian (Lopingian) Gondwanan floras, characterized by the extinction of glossopterid gymnosperms, heralded the end of one of the most enduring and extensive biomes in Earth’s history. The Sydney Basin, Australia, hosts a near-continuous, age-constrained succession of high southern paleolatitude (∼65–75°S) terrestrial strata spanning the end-Permian extinction (EPE) interval. Sedimentological, stable carbon isotopic, palynological, and macrofloral data were collected from two cored coal-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(107 citation statements)
references
References 186 publications
4
102
1
Order By: Relevance
“…This floral change is observed in many areas of Gondwana and was, until recently, interpreted as the terrestrial equivalent of the marine end-Permian biotic crisis 37,38 . More recent discoveries from the Sydney Basin in Australia, however, showed that the collapse of glossopterid dominated forests occurred about 370k years prior to the marine event 6 , although we note the presence there of a long diastem between the last Permian taxa characteristic of the Glossopteris flora and the first post-extinction pollen record 39,40 .…”
Section: Resultscontrasting
confidence: 57%
See 3 more Smart Citations
“…This floral change is observed in many areas of Gondwana and was, until recently, interpreted as the terrestrial equivalent of the marine end-Permian biotic crisis 37,38 . More recent discoveries from the Sydney Basin in Australia, however, showed that the collapse of glossopterid dominated forests occurred about 370k years prior to the marine event 6 , although we note the presence there of a long diastem between the last Permian taxa characteristic of the Glossopteris flora and the first post-extinction pollen record 39,40 .…”
Section: Resultscontrasting
confidence: 57%
“…Hg and TOC values are the average of triplicate analyses of each horizon sampled. Palynological zone assignments, correlated with Australia 39,40 , appear against recovered pollen-and-spore assemblages. See supplemental information for legend.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Most importantly, the end-Permian mass extinction constituted the most severe extinction event for marine animals (e.g., Benton and Twitchett, 2003;Stanley, 2016;Delfino et al, 2020). The timing and impact of this event on the biodiversity of terrestrial animals and land plants is not yet settled (e.g., Benton and Newell, 2014;Cleal, 2014, Cascales-Miñana et al, 2016;Fielding et al, 2019;Nowak et al, 2019;Gastaldo et al, 2020;Mays et al, 2020). However, it is generally accepted that the community structure of terrestrial floras underwent important changes, and there is a growing consensus that these changes should primarily be understood as a matter of successive ecological disturbances, rather than a question of abrupt biodiversity loss (Hochuli et al, 2016;Mishra et al, 2017;Fielding et al, 2019;Nowak et al, 2019;Vajda et al, 2020).…”
Section: Introductionmentioning
confidence: 99%